Principles of managerial finance /Lawrence J. Gitman, Sean Hennessey. - Gitman, Lawrence J.
System requirements for accompanying computer disk: IBM conpatible PC; Microsoft Windows 3.1, Windows 95, or Windows 98; Microsoft Excel version 5.0 or higher.